FORMING LIFE COMPETENCIES AND ENSURING THE ACQUISITION OF SUSTAINABLE DEVELOPMENT GOALS IN THE PROCESS OF INTEGRATED LEARNING IN SECONDARY AND HIGHER EDUCATION (WITH THE EXAMPLE OF COURSES "FOREIGN LANGUAGE" AND "BIOLOGY") - Halyna I. Miasoid; Tetiana I. Yusypiva (Alfred Nobel University Publisher, 2019)
The article is devoted to the study of possibilities of integrated training with the purpose of forming secondary and higher educational institutions students' life competencies and studying the goals of sustainable development in classes of Foreign Language (English) and Natural Sciences, in particular, Biology. The concept of Life competence, its structure, which consists of knowledge, attitudes and life skills, is explored; several framework documents that underlie the development of a competence-based approach to learning were studied, among those documents: the Recommendation of the European Parliament and the Council of the EU on "Key Competences for Lifelong Learning", 2006; Resolution of the UN General Assembly "Transforming our World: The 2030 Agenda for Sustainable Development for the period up to 2030", 2015; the Report "Global Assessment of Educational Programs for Life Skills Training", UNICEF, 2012; Guideline "The Cambridge Framework for Life Competencies", Cambridge, 2018, 2019; "Competence for Life", Atlas Corps, 2018, methodological materials of the IJPOOH project "Educational policy and peer-to-peer education in New Ukrainian school, and "Competent training, favorable for health, safety, successful socialization and self-realization of personality", 2018. It is revealed that the optimal variant of the formation of systemic knowledge of youth about the surrounding world, understanding processes and factors of influence on it and consequences for the planet and humanity, i.e. the formation of a system of life competences and understanding of the goals of sustainable development, is through the integration of training courses "Foreign Language" and "Biology", as well as other related sciences. Some topics are suggested as examples, like "Understanding the Sustainable Development Goals", "What's the Link Between Orang-Utans and the Food We Eat?" and others. Examples are given of forms of learning and teaching methods and learning activities, such as team and group work, research, critical thinking, creative writing, working with video clips, playing games, wall-crawl, presentations, peer assessment and others used to ensure the achievement of the set goal. The sources of educational materials and their combination and adaptation to the age and competency levels of the different stages of education have been suggested.